2014
DOI: 10.1155/2014/173878
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Formation during Acoustic Cavitation: Toward a New Paradigm for Sonochemistry

Abstract: The most recent spectroscopic studies of single bubble (SBSL) and multibubble (MBSL) sonoluminescence reveal that the origin of extreme intrabubble conditions is related to nonequilibrium plasma formed inside the collapsing bubbles. Analysis of the relative populations of OH(A 2 Σ + ) vibrational states observed during MBSL in water saturated with noble gases shows that in the presence of argon at low ultrasonic frequency weakly excited plasma is formed. At high-frequency ultrasound the plasma inside the colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…It was found that gas temperatures inside the bubble are much lower than electron temperatures and do not account for observed emissions. Lower ionisation potentials of the gas provide an increase in electron temperature concurrent with obtained spectra which supports formation of a non-equilibrium plasma [82].…”
Section: Theoretical Backgroundsupporting
confidence: 73%
See 1 more Smart Citation
“…It was found that gas temperatures inside the bubble are much lower than electron temperatures and do not account for observed emissions. Lower ionisation potentials of the gas provide an increase in electron temperature concurrent with obtained spectra which supports formation of a non-equilibrium plasma [82].…”
Section: Theoretical Backgroundsupporting
confidence: 73%
“…The effective temperatures for this process were suggested to be near to 900 K. Sufficiently high temperatures can destroy chemically active components within the bubble. This is concurrent with temperature dependant determination of an ionisation or disassociation process, which in turn can govern the number of reactive species produced [17,25,82,84,85]. For a multibubble sonoluminescence system the pressure inside the bubbles has been estimated to be in the order of 300 bar in argon saturated silicone oil, consistent with adiabatic compression [86].…”
Section: Theoretical Backgroundmentioning
confidence: 87%
“…This type of setting, called Single Bubble SonoLuminescence (SBSL) has been extensively used to observe bubble dynamics and characteristics. 1,51,54,58,59 The spectrum of MBSL in water shows peaks that correspond to excited state OH* (mainly at 310 nm). Solutes can also produce their own lines.…”
Section: Luminescence Fromacoustic and Hydrodynamic Cavitationmentioning
confidence: 99%
“…This could explain the atomic emission lines of noble gases as well as that of non volatile solutes. 59 Most sonoluminescence experiments are conducted in non water liquids, such as concentrated sulphuric and phosphoric acids, glycerine, alkanes, silicone oil, which produce higher light intensities or are more adapted to specific aims, usually further enhanced by noble gas. In contrast, sonoluminescence of untreated water is at least several thousand times weaker.…”
Section: Luminescence Fromacoustic and Hydrodynamic Cavitationmentioning
confidence: 99%
“…The inside of the cavitation bubble at the collapse has a high pressure and a high temperature because of the roughly adiabatic shrinkage. It is believed that a plasma is produced inside the cavitation bubble at the collapse [18,19] (sometimes it is called "sonoplasma") because of the high temperature. The particular physical parameters at the collapse of the cavitation bubble produces reactive radicals.…”
Section: Introductionmentioning
confidence: 99%